Massive Thymic Hyperplasia Mimicking Anterior Mediastinal Neoplasia in Occult Graves' Disease - Kennedy, Christopher James; Paton, David James William (The Thoracic and Cardiovascular Surgeon Reports, 2019)
Background Thymic hyperplasia is a recognized complication of Graves' disease that can present radiologically as an anterior mediastinal mass.Case Description We present a unique case of massive thymic hyperplasia occurring in a 24-year-old female without a known history of thyroid or other systemic disease in whom Graves' disease first manifested intraoperatively during thymectomy for presumed neoplasia.Conclusion We suggest that the work-up of all anterior mediastinal masses should include a comprehensive search for medical causes of reversible thymic enlargement.
Keywords: thymus; thoracic surgery; pathology